2014
DOI: 10.1016/j.cub.2014.05.078
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Learn Opposing Components of a Compound Food Stimulus

Abstract: SummaryDopaminergic neurons provide value signals in mammals and insects [1–3]. During Drosophila olfactory learning, distinct subsets of dopaminergic neurons appear to assign either positive or negative value to odor representations in mushroom body neurons [4–9]. However, it is not known how flies evaluate substances that have mixed valence. Here we show that flies form short-lived aversive olfactory memories when trained with odors and sugars that are contaminated with the common insect repellent DEET. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 34 publications
(67 reference statements)
9
117
0
Order By: Relevance
“…Silencing only one of these dopaminergic neuron populations (MB058B) did not lead to disruption of the taste memory (Figure 2C and Figure S1A) suggesting that the collective action of these dopaminergic neurons may be required. Previous studies showed that PPL1-γ1pedc (MB-MP1) mediates the reinforcing property of electric shock and bitter taste for olfactory and visual learning [28, 3537]. Interestingly, we found a strong impairment of taste memory by MB060B and MB065B, lines that broadly label PPL1 dopaminergic neurons but not the PPL1-γ1pedc (MB-MP1).…”
Section: Resultsmentioning
confidence: 48%
“…Silencing only one of these dopaminergic neuron populations (MB058B) did not lead to disruption of the taste memory (Figure 2C and Figure S1A) suggesting that the collective action of these dopaminergic neurons may be required. Previous studies showed that PPL1-γ1pedc (MB-MP1) mediates the reinforcing property of electric shock and bitter taste for olfactory and visual learning [28, 3537]. Interestingly, we found a strong impairment of taste memory by MB060B and MB065B, lines that broadly label PPL1 dopaminergic neurons but not the PPL1-γ1pedc (MB-MP1).…”
Section: Resultsmentioning
confidence: 48%
“…Strikingly, thermoactivation of the other subset of PAM cluster neurons with R15A04-GAL4 induced robust LTM without forming STM ( Fig. 1 H and I), similar to appetitive memory without a short-term component of mutants for TβH (36). The temporal dynamics of these two forms of memory were Significance A biologically relevant event such as finding food under starvation conditions or being poisoned can drive long-term memory (LTM) in a single training session.…”
Section: Resultsmentioning
confidence: 82%
“…In the T-maze used in flies to measure appetitive (30) and aversive memory (31), flies have to approach or avoid the arm containing the learned odor. When odors are associated with positive and negative rewards at the same time, the flies must decide between approaching or avoiding the odor, thus giving evidence of only one memory (17). In case of olfactory conditioning of proboscis extension in honey bees, the conditioned responses are either extending or withdrawing the proboscis upon stimulation with the odor (15,32).…”
Section: Discussionmentioning
confidence: 99%
“…However, if animals do not form any memory at all or if they form two opposite memories that compete during retrieval is not yet clear. A recent study in Drosophila indicates that appetitive and aversive memories are formed in parallel, and which memory prevails during memory expression depends on the time window in which memory is tested (17). Nevertheless, a limitation in these studies is that aversive and appetitive responses are mutually exclusive, which does not allow concluding whether the memory that is not observed does not exist or its expression is suppressed.…”
mentioning
confidence: 99%